Does a universal non‐contributory social pension make sense for rural China?. (26th May 2020) - Shen, Ce; Johnson, Jessica; Chi, Zhenhe; Williamson, John B.
Abstract: China's pension reform during the past three decades has allowed a majority of China's population to be covered by a pension scheme. Of particular note has been the New Rural Pension Scheme (NRPS), a voluntary programme introduced starting in 2009. One goal of our analysis is to assess that pension scheme, using a variety of sources of information including data drawn from recent (2013 and 2015) nationwide China Health and Retirement Longitudinal Surveys (CHARLS). Our analysis involves an exploration of differences between the generosity and structure of the NRPS and other pension schemes currently in place. We also explore the feasibility of reforming the current "quasi‐social pension" component of the NRPS by substituting a universal non‐contributory social pension pillar. In connection with our assessment of the NRPS, we note the unusually low benefit levels for rural China. Abstract : Au cours des trente dernières années, la réforme des pensions en Chine a permis à la majorité de la population d'être couverte par un régime de pension. Dans ce contexte, nous avons en particulier analysé le nouveau régime de pension rural (NRPR), un programme volontaire introduit à partir de 2009. L'un des objectifs de notre analyse est d'évaluer ce régime de pension, à l'aide de diverses sources d'information, y compris des données tirées des récentes enquêtes longitudinales sur la santé et l'emploi en Chine menées en 2013 et 2015 dans l'ensemble du pays. Nous analysons notamment les différences entre la générosité des indemnités et la structure du NRPR ainsi que d'autres régimes de pension d'ores et déjà mis en place. Nous étudions par ailleurs la possibilité de réformer l'actuelle composante de «pension quasi‐sociale» du NRPR en intégrant un pilier de pension sociale universelle non contributive. Dans le cadre de notre analyse du NRPR, nous constatons un niveau des allocations inhabituellement bas pour la Chine rurale. Abstract : La reforma de las pensiones realizada en China en las últimas tres décadas ha permitido cubrir a la mayoría de la población de China con un régimen de pensiones. En este contexto destacamos el nuevo Régimen de Pensiones Rurales (RPR), programa voluntario introducido en 2009. Uno de los objetivos de nuestro análisis es evaluar dicho régimen utilizandoa diversas fuentes de información, incluidos datos extraídos de recientes encuestas longitudinales sobre salud y jubilación realizadas en China en 2013 y 2015. En nuestro análisis estudiamos las diferencias entre la generosidad y la estructura del RPR y otros regímenes de pensiones existentes. También examinamos la posibilidad de reformar el actual componente de pensión "casi social" del RPR sustituyéndolo por un pilar de pensión social universal no contributivo. En el marco de nuestra evaluación observamos unos niveles de prestaciones inusualmente bajos para la China rural. Abstract : Chinas Rentenreform hat es in den letzten drei Jahrzehnten ermöglicht, die Mehrheit der Bevölkerung Rentensystemen zu unterstellen. Besonders bemerkenswert ist das Neue ländliche Rentensystem ( New Rural Pension Scheme, NRPS), ein freiwilliges Programm, das seit 2009 besteht. Ein Ziel unserer Analyse ist es, dieses Rentensystem gestützt auf eine Vielfalt von Informationsquellen, darunter Daten aus jüngsten (2013 und 2015) landesweiten Langzeiterhebungen über Gesundheit und Renten in China ( China Health and Retirement Longitudinal Surveys, CHARLS), zu beurteilen. Unsere Analyse untersucht die Unterschiede bei Großzügigkeit und Struktur zwischen dem NRPS und anderen heute bestehenden Rentensystemen. Wir prüfen auch die Reformierbarkeit der aktuellen „Quasi‐Sozialrenten"‐Komponente des NRPS durch deren Ersatz durch eine universelle nicht‑beitragsfinanzierte Sozialrentensäule. In Verbindung mit unserer Beurteilung des NRPS stellen wir fest, dass die Rentenniveaus im ländlichen China ungewöhnlich niedrig sind. Abstract : За последние тридцать лет китайская пенсионная реформа позволила включить в пенсионную программу большинство населения страны. Особенно стоит отметить внедрённую в 2009 г. Новую пенсионную программу для сельского населения ( New Rural Pension Scheme ─ NRPS), которая предусматривает добровольное участие. Её оценка является одной из целей нашего анализа, проводимого на основании многих источников информации, в том числе и национальном лонгитюдном исследовании по вопросам здравоохранения и пенсионной системы Китая ( China Health and Retirement Longitudinal Surveys ─ CHARLS) за 2013 и 2015 гг. В работе изучено отличия между выплатами и структурой Новой пенсионной программы для сельского населения и другими действующими пенсионными системами. Также рассмотрено возможность реформирования ныне используемой в этой программе «псевдосоциальной пенсии» и замены её на всеобщую безвзносовую социальную пенсию. По результатам оценки NRPS можно сделать выводы о необычно низком уровне выплат сельскому населению Китая. Abstract : 中国过去30年的养老金改革让大部分的中国人获得养老金制度的保障。特别值得一提的是2009 年推出的被称为"新型农村社会养老保险"(简称新农保)的一项自愿性计划。我们的分析目的之一, 是利用取自多个来源的资料来评估这项养老金方案。这些资料包括取自近期在全中国进行的中国健康与养老追踪调查(2013 与 2015 年)的数据。我们的分析涉及探讨新农保与其它现行养老金方案之间在慷慨度与结构上的差异。我们还探讨了通过替代普惠制非缴费性社会养老金部分从而改革新农保现行"准社会养老金"的可行性。在对新农保进行评估时, 我们注意到了中国农村异常低的福利水平。 Abstract : سمحت الإصلاحات التي أُجريت على نظام المعاشات التقاعدية في الصين خلال العقود الثلاثة السابقة لأغلبية السكان في الصين بالاستفادة من التغطية بخطة المعاشات التقاعدية. ومن الملاحظ بوجه خاص إدراج الخطة الجديدة للمعاشات التقاعدية في المناطق الريفية، وهو برنامج طوعي أُدرج في بداية عام 2009. ومن أهداف هذا التحليل تقييم خطة المعاشات التقاعدية هذه باستخدام مجموعة متنوعة من مصادر المعلومات بما فيها البيانات الأخيرة (2013 و2015) المستمدة من الدراسات الاستقصائية الطولانية التي أُجريت في جميع أرجاء الصين بشأن الصحة والتقاعد في الصين. واستعرضنا في دراستنا الفروق بين سخاء خطة المعاشات التقاعدية في المناطق الريفية وهيكلها وغيرها من الخطط القائمة حالياً. كما استعرضنا مدى إمكانية إصلاح عنصر "المعاشات التقاعدية الشبه اجتماعية" في خطة المعاشات التقاعدية في المناطق الريفية من خلال استبداله بركيزة امعاشات تقاعدية اجتماعية شاملة غير قائمة على الاشتراكات. ولاحظنا، لدى تقييمنا لخطة المعاشات التقاعدية في المناطق الريفية، أن مستويات المنافع منخفضة بشكل كبير في المناطق الريفية في الصين. Abstract : A reforma previdenciária na China ao longo das últimas três décadas possibilitou que a maioria da população chinesa fosse coberta por um regime previdenciário. Destaca‐se o novo regime rural de previdência (NRPS, New Rural Pension Scheme), programa voluntário introduzido a partir de 2009. Um objetivo da nossa análise é avaliar esse regime previdenciário, a partir de diversas fontes de informação, entre as quais dados recentes (2013 e 2015), extraídos de pesquisas longitudinais em saúde e aposentadoria na China ( CHARLS, China Health and Retirement Longitudinal Surveys ) em âmbito nacional. A nossa análise estuda as diferenças entre a generosidade e a estrutura do NRPS e outros regimes previdenciários atualmente em vigor. Também exploramos a viabilidade de reformar o atual componente "quase social da aposentadoria" do NRPS e substituí‐lo por um pilar universal de aposentadoria social não‐contributiva. Aliada à nossa avaliação dos NRPS, observamos os níveis de benefícios incomumente baixos para a China rural.